Continued Educational Neuromyth Belief in Pre- and In-Service Teachers: A Call for De-Implementation Action for School Psychologists. (June 2021) - Craig, Heather L.; Wilcox, Gabrielle; Makarenko, Erica M.; MacMaster, Frank P.
Despite the breadth and depth of educational neuroscience research and teachers' interest in neuroscience, teachers often have limited access to reputable sources. As a result, neuromyths–misapplied or over-simplified claims related to brain science–have proliferated. School Psychologists have training in education, applied neuroscience, and evidence-based practices. As such, school psychologists are poised to mitigate the negative impact of teacher neuromyth endorsement. This study examined the endorsement rate of neuromyths by teachers to identify knowledge gaps to inform future training in this area. In-service and preservice teachers from grades K-12 completed an online survey of common neuromyths. Many neuromyths are pernicious and continue to be endorsed by teachers, most commonly related to learning styles and multiple intelligences. These results support the need for increased training in neuroscience for teachers and suggest a desire for factual and useful information about educational neuroscience, which school psychologists can provide in educational contexts.